Effects of uraemia and dialysis modality on polymorphonuclear cell apoptosis and function - Sardenberg, Camila; Suassuna, Paulo; Andreoli, Maria Claudia Cruz; Watanabe, Renato; Dalboni, Maria Aparecida; Manfredi, Sílvia Regina; dos Santos, Oscar Pavão; Kallas, Esper Georges; Draibe, Sérgio Antônio; Cendoroglo, Miguel (Nephrology, dialysis, transplantation, 2006)
Background. Previous studies have reported that incubation of polymorphonuclear cells (PMN) in uraemic plasma or with different haemodialysis membranes and peritoneal dialysis solutions increases apoptosis in this cell type. In addition, PMN harvested from uraemic patients show a reduced ability to generate superoxide in response to stimuli as well as impaired phagocytosis, chemotaxis and degranulation. The aim of the current study was to investigate the effect of uraemia and dialysis modality on apoptosis and function in freshly harvested non-incubated PMN. Methods. Polymorphonuclear cells were harvested from 14 chronic haemodialysis (HD) patients, from 14 continuous peritoneal dialysis patients (CAPD), 28 chronic kidney disease (CKD), pre-dialysis patients and from 14 healthy subjects (Controls). In these in vivo experiments, PMN apoptosis was studied by means of flow cytometric analysis of annexin V binding to freshly isolated cells. Polymorphonuclear cell phagocytosis and production of reactive oxygen species by unstimulated or stimulated (S.aureus, fMLP, PMA) cells were also studied by flow cytometry using whole blood. Results. We observed increased PMN apoptosis in CKD patients. CAPD and HD patients displayed PMN apoptosis rates similar to controls. In the HD group, PMN exhibited decreased phagocytosis rates. In contrast, phagocytosis rates in PMN from CAPD were not significantly different from controls. In the CKD and HD groups, apoptosis was inversely correlated with respiratory burst activity and phagocytosis. Conclusion. Our results suggest that both uraemia and treatment modality may interfere with PMN apoptosis and function. Dialysis appears to normalize the increased PMN apoptosis rates observed in CKD patients.